Westernmost record of Caulerpa taxifolia var. distichophylla (Chlorophyta, Caulerpaceae) in the Mediterranean: a 20-year journey - MARTÍNEZ-GARRIDO, JOSE; MORENO, DIEGO; ROJO, IRENE; MANCHADO, MANUEL; BARRAJÓN, AGUSTÍN; BERNARDEAU-ESTELLER, JAIME (Mediterranean Marine Science, 2025)
The invasive alga Caulerpa taxifolia has been detected for the first time in the Cabo de Gata-Níjar Natural Park (Andalusia, southern Spain), after more than 30 years of active monitoring for invasive species. Morphological and phylogenetic analyses identified the taxon as C. taxifolia var. distichophylla (Sonder) Verlaque, Huisman & Procaccini 2013, a variety native to Australia and distinct from the aquarium strain introduced in Monaco in 1984. This variety is part of an independent invasion originating in the eastern Mediterranean, first reported in Syria in 2003, which since then has spread westward through the southern Mediterranean Sea. This record from Andalusia represents a significant westward range extension from previous occurrences in Tunisia (2015) and Sardinia, Italy (2016). In just two decades, the species has crossed the Mediterranean from the eastern to the westernmost coasts, demonstrating a remarkable capacity for long-distance dispersal and adaptation to a wide range of habitats. However, compared to the aquarium released C. taxifolia strain, it differs in size, thermal tolerance, and potentially in reproductive traits and secondary metabolite profiles. These differences may determine its potential for spreading and its ecological impact during the ongoing invasion.